Zarys stereotypu Polaka, studenta i blogera w wybranych filmach grupy Abstrachuje. TV - Krzysztoń, Karolina (Słowo. Studia językoznawcze, 2014)
The following paper presents the cultural and linguistic view of the Polishe nation in the selected videos made by Abstrachuje.TV. The analysis is based on three videos which present the reality in a sarcastic way, namely: “Czego NIE mówią: POLACY 2”, “Co mówią: STUDENCI” and “Co mówią: BLOGERZY”. There are three aspects which are taken into consideration. These are: the appearance of Polish people, environment, in which Poles live, mentality of Poles and their language. The cultural and linguistic aspects of Poles presented in the videos are similar to the general stereotype of Polish people. The image of students presented in one of the videos is also negative. Students are described as those who constantly drink alcohol and are not willing to study. On the other hand, they consider themselves as a unique group of extraordinary people. The third video is about bloggers. The main category that makes bloggers special is their language. The distinctions of this language are full of loanwords, the names of computer programs and Internet services and puns.